Mixed methods systematic review and metasummary about barriers and facilitators for the implementation of cotrimoxazole and isoniazid-Preventive therapies for people living with HIV - Müller, Pia (2022)
Funding Information: This study was funded by the Hans-Böckler Foundation (HBS - https://www.boeckler. de) and the Portuguese Foundation for Science and Technology (FCT - www.fct.pt). PM received a Research Scholarship from the HBS (Scholarship ID: 385759). LVL was funded by the FCT grants (UID/Multi/04413/2013 and UID/Multi/04413/2020). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. We would like to express our gratitude to Jonathan O' Mahony for proofreading the manuscript. In addition, we would like to thank Carlos Rodrigues, IT specialist at the Institute of Hygiene & Tropical Medicine in Lisbon, for his support with formatting the graphics included in this manuscript. Publisher Copyright: Copyright: © 2022 Müller, Velez Lapão. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.